Legal Protection for Land Rights Holders and Physical Control According to UUPA - Daulay, Putri Rahmadona; Bhudiman, Budy; Purwaningsih, Prihatini (Universitas Ibn Khaldun Bogor, 2024)
Soil is necessary for every aspect of human life. The government issued Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA). To deal with land rights issues in Indonesia, the Basic Agrarian Law (UUPA) protects rights holders and physical control of land. Article 19 of Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) stipulates that the government carries out land registration to guarantee land rights. Law enforcement is an important part of the UUPA, and the agrarian justice process is included in the mechanisms regulated by law. This research aims to find out how the Basic Agrarian Law (UUPA) protects land rights holders and to find out the role of Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest in protecting land rights holders. The method used in this research is normative legal qualitative. The research results show that the Basic Agrarian Law (UUPA) has a strong juridical foundation in protecting land rights. The principle of legality emphasizes that every government action must have the legitimacy and authority granted by law. Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest has an important role in protecting land rights holders in Indonesia. This law provides a specific legal basis regarding land acquisition for public purposes, with the hope that it can become a legal umbrella and provide adequate protection for land rights holders.